Slang Language Acquisition, Construction, and Context of Used in Teenagers’ Perspective of Batam City - Suhardianto, Ambalegin (Universitas Muhammadiyah Jember, 2017)
Abstract This study aims to find the acquisition, construction and perspectives of adolescents in the use of slang in the city of Batam. This research is a qualitative research used to examine the condition of natural objects where researchers are as a key instrument. In this study, researchers will conduct an investigation by collecting data directly or face to face with the source data and perform descriptive analysis without using statistical procedures or other calculations.The results showed that the formula in the acquisition and construction of slang languages can be seen from seven ways, among others: (a) Abbreviation, (b) Deletion, (c) Letter and sound change, (d) Adoption of Basic Word, (e) English or Indonesian-mixed abbreviation, (f) Citation from other slang languages, (g) New Construction. While the perspective of using slang among teenagers in communicating between them is 30.25% say, they use slang because they want to show other groups that they look more slick and cool, follow the times as much as 27.72%, easier to communicate between them 21% Follow-up friends 7.56%, funny 5.04%, let famous 4.20% and custom 1.64%. Keywords: acquisition, construction, perspective, slang